Meet me at the lake - Fortune, Carley (New York : Berkley, 2023)
In desperate need of a lifeline, 32-year-old Fern Brookbanks finds it in the form of Will Baxter, who rescued her nine years ago, and, believing he is hiding something, but knowing he$1 (Bs the only one who understands what she$1 (Bs going through, wonders if she can do the same for him.s
Includes reader's guide.
Keywords: Man-woman relationships -- Fiction; Strangers -- Fiction; Life change events -- Fiction; Resorts -- Fiction; Business consultants -- Fiction; Muskoka, Lake (Ont.) -- Fiction; Romance fiction